2018
DOI: 10.1080/02656736.2018.1468037
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of novel laparoscopic renal denervation system: a feasibility study

Abstract: We developed a novel laparoscope-based electrosurgical RDN method for hypertension treatment. The feasibility of our system was confirmed through a simulation study as well as in vitro experiments. Our proposed method could be an effective treatment for resistant hypertension as well as central nervous system diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…They evaluated the thermal effectiveness via simulation study on a numerical model designed using histological data and validated the results by the in vitro study. Finally, the simulation results showed that new device is safer and more effective than the existing catheter-based systems [18]. These studies show that RDN from renal artery adventitia pathway is feasible in the treatment of hypertension, which also supports our results.…”
Section: Discussionsupporting
confidence: 86%
“…They evaluated the thermal effectiveness via simulation study on a numerical model designed using histological data and validated the results by the in vitro study. Finally, the simulation results showed that new device is safer and more effective than the existing catheter-based systems [18]. These studies show that RDN from renal artery adventitia pathway is feasible in the treatment of hypertension, which also supports our results.…”
Section: Discussionsupporting
confidence: 86%
“…In in-vivo simulation, the artery 3D, as shown in Fig. 5 was designed based on previous histological studies where the diameter of the artery, the diameter of the lumen, and thickness of the artery wall were 5 mm, 2mm, and 1.5 mm, respectively [17,21]. The arterial wall was composed of tunica media and adventitia.…”
Section: E = −∇V (3)mentioning
confidence: 99%
“…While it cannot be generalized, the lesion depth for the catheter-based RDN was found to be about 2 mm for a cadaver [16] and 6 mm for animal models [17][18][19] from multiple studies, but 31% of renal nerves are located 2-10 mm away from the endoluminal surface [20,21]. Thus, it cannot completely ablate renal sympathetic nerves outside the arterial wall.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations